Black Carbon and Secondary Brown Carbon, the Dominant Light Absorption and Direct Radiative Forcing Contributors of the Atmospheric Aerosols Over the Tibetan Plateau. Issue 11 (5th June 2021) - Zhu, Chong‐Shu; Qu, Yao; Huang, Hong; Chen, Ji; Dai, Wen‐Ting; Huang, Ru‐Jin; Cao, Jun‐Ji
Abstract: Black carbon (BC), primary brown carbon (BrCpri ), and secondary brown carbon (BrCsec ) are important light‐absorbing aerosol. BC and BrC from the surrounding area can reach the Tibetan Plateau (TP) and influence climate change and glacial melting. Here, we presented a study of the light absorption, radiative forcing, and potential source areas of BC and BrC over the northeastern, central, and southwestern TP. The higher light absorption was observed in the northeastern and southwestern sites compared to the central TP site. The major carbonaceous light‐absorbing was attributed to BC with the percentages of 65%, 56%, and 82% in Ngari, Qinghai Lake, and Beiluhe, respectively. The heighten contribution of BrCsec to total light absorption indicated the importance of BrCsec in the TP, especially in the northeastern and southwestern areas. The BrCsec radiative forcings relative to BC were much higher than those of BrCpri . The potential BC and BrCpri source distributions were obtained. Key Points: BC was the dominant light‐absorbing carbonaceous component in the TP The enhanced light absorption and radiative forcing contributions of BrCsec were observed in the northeastern and southwestern TP Major potential source distributions were identified for BC and BrCpri in the TP